Code-Switching As A Communicative Tool For Science Learning In A Chinese Secondary School In Malaysia - Oon , Kim Booy (2011)

(untitled)
In implementing the educational policy of teaching Science and Mathematics in English, policy makers have overlooked the problem in communication faced by both teachers and students in the classrooms. One of the ways, teachers and students use to deal with the problem is to engage themselves in code-switching. Code-switching becomes a problem as it may interfere with the noble aim of improving the command of English through its use as medium of instruction for teaching and learning Science.